2018
DOI: 10.1007/s00103-018-2703-5
|View full text |Cite
|
Sign up to set email alerts
|

Inanspruchnahme kostenfreier verschreibungspflichtiger Verhütungsmittel durch Frauen

Abstract: CFOC seems to be attractive, especially for women with children and those who receive long-term unemployment benefits. Changing demands concerning the safety of birth control during the lives of women should be considered in the discussion about common rules for the access to CFOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…To characterize the study sample, data were reported as mean with standard deviations (SD) for continuous variables and as numbers and percentages for categorical variables. We examined the following factors known to be associated with IUD usage: age, socio-economic status (education, duration of receipt of unemployment benefits, and region of residence) [5, 6, 20, 21], and the exclusive use of less effective contraceptives until free-of-charge contraception was offered [21].…”
Section: Methodsmentioning
confidence: 99%
“…To characterize the study sample, data were reported as mean with standard deviations (SD) for continuous variables and as numbers and percentages for categorical variables. We examined the following factors known to be associated with IUD usage: age, socio-economic status (education, duration of receipt of unemployment benefits, and region of residence) [5, 6, 20, 21], and the exclusive use of less effective contraceptives until free-of-charge contraception was offered [21].…”
Section: Methodsmentioning
confidence: 99%